Role of C - Reactive protein In Carcinoma Esophagus In Terms Of Survival And Disease Free Progression (International Journal of Scientific Research and Management (IJSRM), 2017)
Background: Cancer esophagus carries very poor prognosis. Patients usually present at an advanced stage, when curative options are very limited. There is no independent predictive marker, currently available which may indicate the general status of the patient prior to treatment. Keeping in view the poor outcome and great load of this diseases in this part of country, we conducted this study to find out the significance of C - reactive protein levels in our set of patients. Material and methods: A total of 153 patients with histologically confirmed carcinoma esophagus, were enrolled in the study between November 2013 to May 2015.Patient’s eligibility included Squamous cell carcinoma histology, No prior treatment in the form of surgery, chemotherapy or radiotherapy. History of the patient was thoroughly taken to rule out any chronic illness. Besides CBC, biochemistry, imaging modalities used for staging workup, serum C-reactive protein levels were determined in all patients prior to treatment.